Education of female children in Serbia in the first half of XIX century - Stojanović-Jovanović Biljana; Jovanović Stevan (University of Kragujevac - Faculty of Pedagogy, Užice, 2017)
This paper discusses the education of female children in the nineteenth and early twentieth century, having in mind the fact that in the XIII and the beginning of XIX century there was no educational system in Serbia in the true sense of the word, and that only a few boys and girls had the opportunity to attend classes. In the first decade of the nineteenth century, for the first time in this region, the idea of women's education has been accepted by the authorities, but only partially. From 1842 to 1858, a network of women's public schools started to develop, but slowly. The first schools for females didn't have specifically prescribed curricula; they were practically the same as in the schools for boys, except for grammar, geography, history, stylistics, knitting and embroidery. Literacy in Serbia rose from 4.2 percent in 1866 to 11 percent in 1884. The most radical reforms were envisaged in 1882, but if they had actually been implemented, that would have been a major step forward for women's education. At the beginning of the twentieth century the coverage of girls being educated, despite the legal obligation, was only 17 percent, and the proportion of illiterate women was still high, particularly because of inadequate access to basic education of rural youth. With urbanization, as one of the indicators of progress, the number of literate young women grew, but only in cities.